CONGENITAL ABSENCE OF PULMONARY ARTERY - HAYAT , FS; REHMAT , S; AHMAD , J; KHAN , B; IKHTIAR , Z; BADSHAH , I; KHAN , S; BADSHAH , Y; KHATTAK , KU; UMAR , Z (Biological and Clinical Sciences Research Journal, 2024)
Isolated unilateral absence of a proximal pulmonary main artery is a rare congenital condition with a prevalence of 1 in 200,000 (1). The first case was reported in 1868, and to date, 350 cases have been reported (2). It usually occurs in conjunction with other cardiovascular anomalies such as tetralogy of Fallot, VSD, truncus arteriosus, etc. (2), and is typically diagnosed in childhood. Survival into adulthood is rare. Symptoms of this condition can include shortness of breath, chest pain, hemoptysis, reduced exercise tolerance, pleural effusion, and recurrent infections. We encountered a case of a 22-year-old female presenting with these symptoms. Initially, the symptoms suggested pulmonary embolism. However, further investigation through CTPA and Echocardiography revealed the absence of the left pulmonary artery. This case report emphasizes that patients showing signs and symptoms indicative of PAH should also be evaluated for the absence of a pulmonary artery." The pulmonary arteries originate from the sixth aortic arch during the sixteenth week of normal embryonic development. The proximal segment of the 6th aortic arch forms the initial portion of the right & left pulmonary arteries, respectively. The link on the arch’s right side vanishes, whereas it establishes a connection through the ductus arteriosus on the left side. Pulmonary artery agenesis arises from the aberrant rotation of the afflicted segment’s attachment to the aortic arch and dysfunctions during migration (3). Certain publications utilize the phrase “proximal blockage of the pulmonary artery” instead of “agenesis” to describe this anomaly. Although the intraparenchymal distal segment of the pulmonary artery is miniature, it is safeguarded (4). The prevalence of bronchopneumonia is ascribed to multiple causes, such as diminished lung tissue perfusion, impaired mucosal defense, and a possible unbalance of protease-antiprotease enzymes. Moreover, increased collateral blood flow may be associated with the onset of hemoptysis.